2015
DOI: 10.15184/aqy.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Plankboat skeuomorphs in Bronze Age logboats: a Scandinavian perspective

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The Lee's Island boat has been dated to 3023 ± 27 BP (1390-1134 cal BC, 2-sigma) and, whilst it is still a logboat, the use of similar sewn plank boat technology to repair the splits provides the earliest evidence for the existence of such technology in Ireland during this period. The emerging evidence for the wider use of plank built boats outside of Britain is also being highlighted (Crumlin- Pedersen and Trakadas 2003;Kastholm 2015;, with a number of Bronze Age and Iron Age examples from Denmark and Norway now identified. Consequently, the plank boat technology observed in the Lee's Island logboat can also be viewed as an 'indicator of a broader interregional tradition of plankbuilding in Western Europe' as noted by Kastholm (2015Kastholm ( : 1369.…”
Section: Evidence For Communication Transfer Of Ideas and Technologic...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Lee's Island boat has been dated to 3023 ± 27 BP (1390-1134 cal BC, 2-sigma) and, whilst it is still a logboat, the use of similar sewn plank boat technology to repair the splits provides the earliest evidence for the existence of such technology in Ireland during this period. The emerging evidence for the wider use of plank built boats outside of Britain is also being highlighted (Crumlin- Pedersen and Trakadas 2003;Kastholm 2015;, with a number of Bronze Age and Iron Age examples from Denmark and Norway now identified. Consequently, the plank boat technology observed in the Lee's Island logboat can also be viewed as an 'indicator of a broader interregional tradition of plankbuilding in Western Europe' as noted by Kastholm (2015Kastholm ( : 1369.…”
Section: Evidence For Communication Transfer Of Ideas and Technologic...mentioning
confidence: 99%
“…The emerging evidence for the wider use of plank built boats outside of Britain is also being highlighted (Crumlin- Pedersen and Trakadas 2003;Kastholm 2015;, with a number of Bronze Age and Iron Age examples from Denmark and Norway now identified. Consequently, the plank boat technology observed in the Lee's Island logboat can also be viewed as an 'indicator of a broader interregional tradition of plankbuilding in Western Europe' as noted by Kastholm (2015Kastholm ( : 1369. Nevertheless, this raises an intriguing question: if sewn plank boat building techniques were known, why did they not supersede logboats?…”
Section: Evidence For Communication Transfer Of Ideas and Technologic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Boat remains in Scandinavia predating the Iron Age include log boats dating back to the Mesolithic in Denmark and the Bronze Age on the Scandinavian Peninsula (Lanting 2000;Kastholm 2015) and a bark canoe from Byslätt in south-western Sweden recently dated to 900-800 BC (Von Arbin and Lindberg 2017). These vessels were arguably designed for inland waters or nearshore use.…”
Section: Boats Written In Stone: Rock Art and Reality In The First Mi...mentioning
confidence: 99%
“…These vessels were arguably designed for inland waters or nearshore use. Kastholm (2015) has demonstrated that a considerable number of Bronze Age log boats have features that mimic plank-built boats as yet undocumented outside Britain, thus signaling participation in a larger maritime network (Van de Noort 2006). The earliest remains of a true seagoing vessel in Scandinavia is the Hjortspring boat from southern Denmark dated to c. 350 BC (Crumlin-Pedersen and Trakadas 2003;Kaul 2003a).…”
Section: Boats Written In Stone: Rock Art and Reality In The First Mi...mentioning
confidence: 99%